Cowpea–Plantain Composite Flour: An Educational Approach to Dietary Intervention for Blood Pressure Management - Zulfiana Dewi; Sajiman Sajiman (Jurnal Penelitian Pendidikan IPA, 2026)
Hypertension is a major risk factor for cardiovascular diseases and remains highly prevalent in Indonesia, particularly in South Kalimantan. This study aims to formulate a cowpea–plantain composite flour as a functional food with synergistic potential for blood pressure regulation. Composite flours were produced by processing raw materials through drying, milling, and sieving into formulations ranging from 10:90 to 90:10. Sensory attributes, including color, aroma, texture, and taste, were evaluated by 30 panelists, and the best formulation was determined using the De Garmo effectiveness index. Proximate composition, mineral content (potassium and sodium), and amino acid profiles were analyzed in an accredited laboratory. Sensory evaluation revealed that higher proportions of cowpea decreased taste acceptability, whereas plantain improved organoleptic characteristics. The optimal formulation was identified as KTPR8020 (80% cowpea : 20% plantain), which achieved a balanced profile of texture, aroma, and taste. Nutritional analysis indicated that cowpea increased protein (17.50%) and fat (1.56%) contents, while plantain contributed mainly to carbohydrates. The KTPR8020 formulation contained 5.98 mg/100 g potassium with a K/Na ratio of 7.1, supporting potassium-induced natriuresis. Amino acid profiling showed dominance of lysine, leucine, isoleucine, valine, and arginine, which are known precursors of bioactive peptides with ACE-inhibitory activity